Assessment of Nurses' Knowledge Towards Child with Bacterial Meningitis at Pediatric Teaching Hospitals in Baghdad City - Tofieq, Narmein; Al-Rubayi, Haleema (Iraqi National Journal of Nursing Specialties, 2007)
Objective: the aim of the study is to assess the knowledge and practices for nurses that working inwords of Ibn Al-kuff hospital for spinal cord injuries.Methodology: descriptive study from the period of (1st of July to the 30th August 2005) about theknowledge and practical management when autonomic dysreflexia syndrome affects those patientswhom sleeping in the words of this hospital and its relationship with some variables.The sample of the study consists of (100) nurses male and females are selected purposively. aquestionnaire check list was designed for study purpose and applied by (test - retest) to improve thereliability, the validity of the assessment was determined through a panel of experts.The data analyzed by using descriptive statistical approach (frequency, percentage, mean of score, test)and inferential data analysis approach (chi-square).Results: the finding of the study indicated that the large number of these nurses did not have enoughknowledge and practices about autonomic dysreflexia syndrome management during its occurrence.Recommendation: the researchers suggested that especial education program should be developed andimplemented for these nurses who work in the spinal cord injuries wards, the program should include,knowledge and practices relative to general, sings and symptoms, causes nursing intervention of theautonomic dysre flexia.